Do screening ao mecanismo de ação, uma contribuição para a descoberta de ciclopaladados bioativos: a atividade leishmanicida de CP2 e seu efeito inibitório frente à DNA topoisomerase 1B de Leishmania - Velásquez, Angela Maria Arenas [UNESP] (2017)
Leishmaniasis are diseases globally distributed in tropical and subtropical areas of the world and Leishmania spp. are the etiological agents of the diseases. Numerous problems associated with available treatments of the disease are still unsatisfactory because currently available drugs are highly toxic, little effectiveness and drug resistance cases have emerged. Furthermore, leishmaniasis are a neglected disease by pharmaceutical industries and governments. In the search for new drugs with a broad spectrum of action and low toxicity, there is evidence to suggest that transition metal complexes can act in several compartments or organelles of protozoa, as well as to present low toxicity in the mammalian host. In this work, we evaluated the leishmanicidal and trypanocidal in vitro activity of six cyclopalladated compounds: [Pd(dmba)(µ-Cl)]2 (CP1), [Pd(dmba)(µ-N3)]2 (CP2), [Pd(dmba)(µ-NCO)]2 (CP3), [Pd(dmba)Cl(isn)] (CP4), [Pd(dmba)(N3)(isn)] (CP5), [Pd(dmba)(NCO)(isn)] (CP6) and the free ligands, Hdmba: N,N- dimethylbenzylamine e isn: isonicotinamide. The cyclopalladated complexes CP2 inhibited the growth of the promastigote forms of Leishmania amazonensis (IC50 = 13,2 ± 0,7 µM), reduced the proliferation of intracellular amastigote forms (IC50 = 10,2 ± 2,2 µM) and showed a low cytotoxic effect against peritoneal macrophages (CC50 = 506,0 ± 10,7 µM). In vitro assays against T. cruzi and T. brucei, parasites that cause Chagas disease and sleeping sickness, respectively, demonstrated that cyclopaladate compounds have a wide spectrum of action and constitute an excellents candidates for the treatment of these neglected diseases. CP2 was at least fifty-times more selective for intracellular amastigote forms of L. amazonensis and two hundred-times more selective for intracellular amastigote forms of T. cruzi vs. mammaliam cells. For in vivo assays, CP2 (0.35 mg/Kg/day) was not toxic to BALB / c mouse infected with L. amazonensis, no changes were observed in biochemical markers of renal/hepatic function, in in silico studies showed a 100% of permeability for intestinal absorption and the parasite load of the animals was reduced to 80%, like amphotericin B (2 mg/Kg in alternate days), the drug currently used in the leishmaniasis treatment. In-depth studies of the mechanism of action have shown that CP2 can inhibit the cleavage step of Leishmania DNA Topoisomerase 1B. Comparative proteomic analysis (two-dimensional electrophoresis, followed by mass spectrometry) were performed to identify proteins differentially expressed in L. amazonensis in the absence / presence of CP2 and thus to determine molecular events generated from the inhibition of parasite DNA Topoisomerase. We found in the proteomic analysis chaperonins associated with different stresses (calreticulin, putative 10 kDa heat shock protein, putative heat-shock protein hsp70, putative glucose-regulated protein 78, protein disulfide-isomerase), proteins that act in the process of cellular detoxification (trypanothione reductase, peroxidoxin, tryparedoxin peroxidase) and other proteins associated with several biological processes associated with a possible programmed cell death in Leishmania.